Implementasi Algoritma Arithmetic Coding Pada Aplikasi Kompresi File PDF - Prades, Egi (Jurnal Sains dan Teknologi Informasi, 2024)
Currently, application users use information more and more commonly. However, there is a problem that is often encountered, namely the need for large data so that less storage space is needed. Apart from that, the small amount of storage space also affects the speed of sending data. One of the data that is often used is PDF format files. The solution to this problem is to compress the PDF file. Compression is a process of changing a collection of data into a form of code to save on data storage requirements so that the data used is not too large. The Arithemtic Coding algorithm is a data compression algorithm that can be used, by knowing the results of the compression ratio and redundancy process. In applying the Arithmetic Coding algorithm in this research, it can provide compression results which initially have a large size which can be compressed very well in PDF files and the compression results show a compression ratio of 2.15 while the Compression ratio is 46% and Redundancy 54% will be beneficial in sending and moving PDF files will be even easier